Znaczenie procesu metropolizacji w zglobalizowanym świecie - Brzozowska, Katarzyna; Robak, Roksana (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
A sudden increase of urbanization is one of main features of today’s economy. There are around 400 cities with more than 1 million inhabitants in the world, from which one third is located in Asia. Just the metropolitan region of Tokyo-Yokohama has 34 millions of inhabitants or New York City with 22 millions. If that trend maintains, what is virtually certain, within a few years, 60% of population will become metropolises’ inhabitants. Full consequences of this process is hardly to forecast. One is certain — cities will keep on growing and it will especially concern the vastest centers — metropolises. In that face, government of cities’ development acquires great significance — boosting their competitiveness should go along with rules of sustainable development.The dissertation is an attempt to present evolution from city — passive unit, which posses givenconditions — to metropolis, which is an active participant of the global economy, with all its consequences for both: national and global economies. The authors tried to find answers for such questions like: what is the competition between metropolises and its results, what regions compete for. On the basis of the global tendencies there have been drawn Polish cities’ ‘metropolitan power’ and its perspectives for development.
Keywords: metropolizacja; urbanizacja; globalna gospodarka